Root carbon and soil temperature may be key drivers of below-ground biomass in grassland following prescribed fires in autumn and spring - Luo, Chaoyi; Fang, Zhao; Liu, Jiang; Han, Fengpeng; Wu, Yanhong; Bing, Haijian; Zhao, Peng (Journal of environmental management, 2024)
Under global warming, fire and the season in which the fire occurs both have important impacts on grassland plant biomass. Still, the effect of fire on below-ground biomass (BB) along a natural aridity gradient and the main impact factors remain unclear. Here, we conducted a fire manipulation experiment (including un-fired, autumn fire and spring fire treatments) to investigate the effects of prescribed fire on BB and its critical determinants along a transect of grassland in northern China. BB had different response strategies in different aridity regions and fire seasons, despite above-ground biomass (AB) and root-shoot ratio were not significantly affected by fire. General linear regression models revealed that the fire changed the trend of increasing BB to decreasing along increasing aridity (p ＜ 0.05). Random forest model (RFM) and partial correlations revealed that the BB was primarily influenced by aridity, followed by the nitrogen (N) and phosphorus (P) concentration ratio of AB under un-fired disturbance. For autumn fire, the BB was primarily influenced by below-ground biomass carbon concentration (BB c), followed by the C and N concentration ratio of BB. For spring fire, the BB was primarily influenced by soil temperature (ST), followed by aridity and soil total phosphorus concentration (Soil p). Furthermore, partial least squares path model (PLS-PM) revealed that autumn fires weakened the effects of environmental factors on BB, while spring fires enhanced the effects of soil nutrients on BB. These suggested that fire disrupted the original stable nutrient dynamics of BB. Our results suggested that fire promoted the growth of BB in relatively humid areas (aridity = 0.51–0.53) while inhibited the growth of BB in relatively arid areas (aridity = 0.68–0.74). BB c and ST may be key drivers of BB after prescribed fire in autumn and spring. •The prescribed fire changed the trend of increasing belowground biomass to decreasing along with increasing aridity.•The belowground biomass of plants was mainly regulated by belowground biomass C after prescribed fire in autumn.•The belowground biomass of plants was mainly regulated by soil temperature after prescribed fire in spring.•The prescribed fire disrupted belowground biomass's original stable nutrient dynamics.